ANALISIS YURIDIS PERLINDUNGAN HUKUM PEREMPUAN DI BAWAH UMUR DALAM PERKAWINAN DI INDONESIA BERDASARKAN UNDANG-UNDANG NOMOR 16 TAHUN 2019 - Pangeran Ramadhan Putra; Niru Anita Sinaga (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2025)
This study analyzes the legal protection of underage girls in marriage in Indonesia based on Law Number 16 of 2019. Although this law has raised the minimum age for marriage to 19 years, this study uses normative legal methods with case, statutory, and conceptual approaches, as well as qualitative analysis of legal materials. The practice of child marriage of girls remains high due to gaps in the marriage dispensation mechanism by the Religious Courts. Multiple interpretations of